The Prevalence of methicillin resistant Staphylococcus aureus and methicillin resistant Staphylococcus epidermidis in AL-Sulaimania city - Muhammad, Hemn; Al-Mathkhury, Harith (Iraqi Journal of Science, 2023)
One hundred thirty seven Staphylococcus spp. isolates were isolated form one hundred fifty clinical specimens which were collected from several hospitals at Al-Sulaimaniya city. Seventy two Staphylococcus aureus isolates, 28 Staphylococcus epidermidis isolates and 37 isolates related to other coagulase negative staphylocci (S. chromogenes, S. lugdunensis, S. cohnii, S. saprophyticus, S. hominis, and S. haemolyticus constituted 3.60%, 2.20%, 2.90%, 2.90%, 6.60%, and 8.80%, respectively). Burn specimens represented the highest (P< 0.05) reservoir for S. aureus and S. epidermidis isolates. Staphylococci developed variable susceptibility to 4 antibiotics (cefoxitin; 30 μg, oxacillin; 1μg, methicillin; 5μg, and cefotaxime; 30 μg). Nevertheless, the results revealed that 68, 93, and 92% of S. aureus, S. epidrmidis, and other Coagulase negative staphylococci (CONS) isolates developed methicillin resistance based on cefoxitin diffusion disc test. In a conclusion, methicillin resistant S. aureus (MRSA) and coagulase negative staphylococcus sp. (MRCONS) is an emerging subject even in our community, which requires further attention and support.